THERMOKINETIC STUDY OF FORMATION OF CARBON MONOXIDE IN THE DIMERISATION OF ISOCYANIC ACID - Tho, Nguyen Huu; Tri, Nguyen Huu (Hue University Journal of Science: Natural Science, 2018)
The mechanism of the dimerization of HNCO was investigated using the ab initio method. The barrier heights, reaction energies and geometrical parameters of the reactants, products, intermediates and transition state were studied. It was found that there are possibly three reaction channels. The B3LYP 6-311++G(3df,2p)//CCSD(T) 6-311++G(d,p) calculated barriers show that reaction of formation of four-membered ring O=CNHNHC=O is more favorable than formations of CO2 or CO. The reaction pathway of the formation of carbon monoxide from the dimerization of isocyanic acid is a new pathway. Its rate constant is very small, k = 2.62´ 10-19 cm3/molecule/s at 2500K, 1atm, which is about 2000 times as small as rate constant of formation CO from a bimolecular mechanism of HNCO with Ar.